Preparation of plant growth promoter oligoβ-glucan by gamma irradiation - Le , Quang Luan; Nguyen , Huynh Phuong Uyen (Nuclear Science and Technology, 2013)
The β-glucan extracted from the yeast cell wall was irradiated by gamma rays from a Co-60 source at doses from 100 to 300kGy in swelling condition of 10% (w/v) for degradation. The water soluble content of irradiated sample increased from 25.89 to 66.71% by the increasing of doses from 100 to 300kGy. While the molecular weight of water soluble β-glucan was found to be decreased from 48.13 (at 100kGy) to 10.77 kDa (at 300kGy). The UV-spectra of resultant water soluble β-glucan were appeared a new peak at 265nm with the intensity increased by the increase of the dose. The IR spectra of irradiated β-glucan samples were also recognized by an increase of peak intensity at 1731cm-1 assigned to C=O linkages and a decrease of peak intensity at 1156cm-1 assigned to C-O-C glycosidic linkages by the increasing of dose. In addition, the oligoβ-glucan with Mw about 18 kDa obtained at 250kGy-irradiated sample strongly promoted the growth of mustard green and lettuce. The oligoβ-glucan prepared by radiation techniques showed as a high effective plant growth promoter. This product is potentially promising for application in high-technological agriculture for production of clean vegetables and agro-products.